Phytophthora capsici homologue of the cell cycle regulator SDA1 is required for sporangial morphology, mycelial growth and plant infection. (27th August 2015) - Zhu, Chunyuan; Yang, Xiaoyan; Lv, Rongfei; Li, Zhuang; Ding, Xiaomeng; Tyler, Brett M.; Zhang, Xiuguo
Summary: SDA 1 encodes a highly conserved protein that is widely distributed in eukaryotic organisms. SDA1 is essential for cell cycle progression and organization of the actin cytoskeleton in yeasts and humans. In this study, we identified a P hytophthora capsici orthologue of yeast SDA 1, named PcSDA 1. In P . capsici, PcSDA 1 is strongly expressed in three asexual developmental states (mycelium, sporangia and germinating cysts), as well as late in infection. Silencing or overexpression of PcSDA 1 in P . capsici transformants affected the growth of hyphae and sporangiophores, sporangial development, cyst germination and zoospore release. Phalloidin staining confirmed that PcSDA 1 is required for organization of the actin cytoskeleton. Moreover, 4′, 6‐diamidino‐2‐phenylindole (DAPI) staining and PcSDA 1‐green fluorescent protein (GFP) fusions revealed that PcSDA 1 is involved in the regulation of nuclear distribution in hyphae and sporangia. Both silenced and overexpression transformants showed severely diminished virulence. Thus, our results suggest that PcSDA 1 plays a similar role in the regulation of the actin cytoskeleton and nuclear division in this filamentous organism as in non‐filamentous yeasts and human cells.